Students' Perceptions of Learning Mathematics Online - Nova Rita Andriani; Daharnis Daharnis (Counseling and Humanities Review, 2021)
This research was motivated by a change from direct learning to online learning. This is due to the Covid-19 pandemic that occurred in early 2020. There are students who think that learning Mathematics online is difficult. So that students have negative perceptions about learning Mathematics online. This study aims to describe students' perceptions about learning Mathematics online in terms of the stages before learning, while studying, and after learning. This research uses a descriptive approach with quantitative methods. The population in this study was students of SMA UNP Laboratory Construction for the 2020/2021 academic year, totaling 621 and sample 243 students. The sample selection used simple random sampling technique. The data collection technique used a questionnaire on students' perceptions about learning Mathematics online with a Likert scale model. Data were analyzed using descriptive statistical analysis techniques. This research as a whole shows that the students' perceptions about learning Mathematics online at the UNP Laboratory Development High School as a whole are in the quite good category with a percentage of 60%. Furthermore, seen from the aspect of the stages before learning is in the quite good category, namely 65%, Then, seen from the aspects of the stages during learning, it was in the quite good category, namely 60%, and seen from the aspect of the stages after learning is in the quite good category, namely by 66%. The implication of this research can later be used as a consideration of guidance and counseling in the school.